Teka-Teki Silang dan Video Animasi Meningkatkan Pengetahuan Gizi Seimbang pada Anak Usia Sekolah - Andita Arifianita Putri; Utami Wahyuningsih; Nur Intania Sofianita; Iin Fatmawati (HB PRESS, 2022)
Nutritional problems in school-age children can occur because of less knowledge. School-age period is the right time for provide nutrition education. Nutrition education needs the interesting and fun media to make it easier to understand, such as crossword puzzles and animation videos. This study aims is to determine the influence of nutrition education with crossword puzzles and animation videos on balanced nutrition knowledge in school-age children. The methods that used is a quasi-experimental with a pretest and posttest group design. The 54 students aged 10 to 12 from fifth graders were selected by stratified random sampling and divided into two media groups. The statistical tests utilized are the independent and paired sample t-tests. The majority of responders were male (63%) and 11 years old (79.6%). The results showed that there were differences in the influence of nutrition education before and after being given crossword puzzles (p = 0.003) and animation video (p = 0.000) on balanced nutrition knowledge. The results also showed that there was no difference in the effectiveness of nutrition education between crossword puzzles and animated videos on balanced nutrition knowledge (p = 0.987). Crossword puzzles and animation videos have an impact for given balanced nutrition education on school-aged children. Animation videos is more effective in increasing balanced nutrition knowledge on school-age children compared to crossword puzzles. It is recommended that the government and schools implement nutrition education initiatives using engaging and entertaining media, such as animation videos.